Towards Real-Time and Affordable Strain-Level Metagenomics-Based Foodborne Outbreak Investigations Using Oxford Nanopore Sequencing Technologies - Buytaers, Florence E.; Saltykova, Assia; Denayer, Sarah; Verhaegen, Bavo; Vanneste, Kevin; Roosens, Nancy H. C.; Piérard, Denis; Marchal, Kathleen; De Keersmaecker, Sigrid C. J. (Frontiers in Microbiology, 2021)
The current routine laboratory practices to investigate food samples in case of food-borne outbreaks still rely on attempts to isolate the pathogen in order to characterize it. We present in this study a proof-of-concept using shiga toxin-producing Escherichia coli for a strain-level metagenomics food-borne outbreak investigation method using the MinION and Flongle flow cells from Oxford Nanopore Technologies. This approach offers the advantage of being more time and cost-efficient, if limited samples are involved, as compared to Illumina short read based metagenomics for outbreak source attribution. After 12 hours of MinION sequencing, strain-level characterization could be achieved, linking the food containing a pathogen to the related human isolate of the affected patient, by means of a SNP-based phylogeny, with the use of long reads applying a bioinformatics method based on reference-based classification. The same result could be obtained after 24 hours sequencing on the more recent lower-output Flongle flow cell, on an extract treated with eukaryotic host DNA removal. Moreover, an alternative approach based on in silico DNA walking allowed to obtain rapid confirmation of the presence of a putative pathogen in the food sample. This was achieved after sequencing only 1 hour with the MinION, 1 hour with the Flongle if using a host DNA removal extraction or 5 hours with the Flongle with a classical DNA extraction. This paves the way towards the use of metagenomics as a rapid, simple, one-step method for food-borne outbreak investigation that can be implemented in routine laboratories on samples prepared with the current standard practices.